Mapping the field: A bibliometric analysis of oral tradition research in Indonesia - Andalas, Eggy Fajar; Prawiroatmodjo, Sudibyo; Saktimulya, Sri Ratna; Wulandari, Arsanti (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
The study of oral traditions in Indonesia has a long history, dating back to the Dutch colonial period. The field developed following the country's independence. Subsequently, it received support from the Balai Pustaka and the Regional Government Language Center in the post-New Order period. Nevertheless, the current state of knowledge remains undocumented. This study employs bibliometric methods to map the knowledge landscape of oral tradition research in Indonesia over a 44-years (1980-2024), focusing on performance analysis and science mapping. This research analyzed 139 documents from 102 sources written by 312 authors from 10 countries from the Scopus database. The results indicate an increase in publication trends over the past nine years. The Malay World is the most prolific journal in terms of oral tradition research output in Indonesia. Research themes related to disasters and the environment have emerged as a significant area of interest. Fourth G is the most productive author in this field. The science mapping analysis indicates that oral tradition research in Eastern Indonesia is emerging as a new field of study. Topics on wisdom and the environment are unique to oral tradition research in Indonesia, and emerging themes are related to using oral tradition in education. Future research areas include ecological wisdom, regional architecture, and traditional ecological knowledge. These findings provide an overview of the development and direction of oral tradition research in Indonesia and insight into the current position of oral tradition research in the country. They are also helpful for researchers and decision-makers seeking a deeper understanding of the current state of oral tradition research in Indonesia.